A negative electrode and battery based on sieving carbon
The orifice structure of carbon materials was adjusted through two chemical vapor deposition methods, which solved the problem of excessive orifice size of amorphous carbon materials, improved its first Coulomb efficiency and commercial application potential, and achieved efficient electrochemical performance improvement.
Patent Information
- Application Number
- CN202410618379.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-06
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-02-06
AI Technical Summary
The electrochemical properties of amorphous carbon materials are limited by their microstructure, especially their orifice structure, resulting in the inefficiency of the first Coulomb, hindering its commercialization process.
The orifice size of carbon material is adjusted by two chemical vapor deposition methods. The first time the orifice is quickly reduced at high temperature, and the second time the orifice diameter is repaired at low temperature is less than 0.33nm to ensure that the carbon deposited periphery of the orifice will not enter. In the hole, maintain the original size of the hole.
It significantly improves the first Coulomb efficiency of carbon materials, enhances its commercial application potential, and avoids excessive deposition and in-pore deposition through fine regulation of the orifice structure, and improves sodium storage capacity and electrochemical performance.
Smart Images

Figure CN118579784B_ABST
Abstract
Description
[0001] This invention application is a divisional application of the parent application "A screening type carbon and its preparation method and application". The application number of the parent application is 2024101662436 and the application date is February 6, 2024. Technical Field
[0002] The present invention relates to the technical field of electrode materials, and in particular to a negative electrode and a battery based on screening carbon and a preparation method and application thereof. Background Art
[0003] Amorphous carbon materials are the most commercially promising battery negative electrode materials due to their low cost, low operating potential and excellent cycle stability. However, amorphous carbon materials currently face the problem of low first coulombic efficiency, which seriously hinders their commercialization process.
[0004] The electrochemical properties of amorphous carbon materials are closely related to their microstructure, especially the pore structure of carbon materials directly affects their first coulombic efficiency. The Chinese patent application "High-energy and high-power carbon materials and preparation methods and sodium-ion batteries" with publication number CN116553547A discloses a high-energy and high-power carbon material with a pore diameter of 0.1-0.4nm. However, the pore diameter of 0.4nm is still too large, which is not conducive to the first coulombic efficiency, and the pore size needs to be further controlled.
[0005] The present invention discloses a screening carbon and a preparation method and application thereof. The pore size of the screening carbon can be lower than 0.33 nm after two size adjustments, and there is no pore size of 0.33 nm to 0.4 nm. The first coulomb efficiency is significantly improved. Summary of the invention
[0006] The purpose of the present invention is to provide a screening type carbon to solve the problem of excessively large pore size of carbon materials in the prior art.
[0007] Another object of the present invention is to provide a method for preparing the screening carbon.
[0008] Another object of the present invention is to provide application of the sieve-type carbon in battery electrodes.
[0009] The technical solution adopted to achieve the purpose of the present invention is:
[0010] A screening carbon, wherein the pore opening and the periphery of the pore opening are deposited with primary deposited carbon, the surface of the primary deposited carbon is deposited with secondary deposited carbon at the position of the pore opening, the two deposited carbons do not enter the pore belly, the pore opening diameter after the two depositions is less than 0.33nm, and the specific surface area of the screening carbon after CO2 adsorption and desorption test is 0-10m 2 / g.
[0011] In the above technical solution, the pore diameter of the screening carbon is 0.5-10nm.
[0012] Another aspect of the present invention is a method for preparing screening carbon, comprising the following steps:
[0013] Step 1, the first chemical vapor deposition to quickly reduce the pore size: placing the porous carbon in a chemical vapor deposition device, introducing a predetermined flow of protective gas, heating to 1100-1300° C., and then introducing a predetermined flow of the first carbon source gas, and performing the first heat preservation;
[0014] Step 2, second chemical vapor deposition to fine-tune the orifice to a diameter less than 0.33 nm: after the first heat preservation, the first carbon source gas is cut off, the temperature is lowered to 600-800° C., and the second carbon source gas with a predetermined flow rate is introduced for the second heat preservation;
[0015] Step 3, closing the second carbon source gas and cooling the temperature to room temperature at a predetermined cooling rate to obtain the screening carbon.
[0016] like Fig.17 As shown, the temperature of the first chemical vapor deposition (rapid shrinkage of the pore) is 1100-1300°C. At this temperature, the carbon source gas is rapidly cracked and deposited, sacrificing the selectivity of the carbon source gas deposition at the pore mouth (partial deposition occurs outside the pore) and causing it to rapidly shrink the pore mouth. The pore mouth is a defect site, and the rapidly cracked carbon source gas is mainly deposited at the pore mouth, with a small amount of deposition outside the pore. If the temperature is lower than 1100°C, the purpose of rapidly shrinking the pore mouth cannot be achieved, and the pore mouth shrinkage rate is slow, causing the deposited carbon to enter the pore. If the temperature is higher than 1300°C, the deposition rate is too fast, and the pore mouth may be sealed instantly, resulting in excessive ineffective carbon deposits.
[0017] The temperature of the second chemical vapor deposition (refining the pore to a diameter less than 0.33nm) is 600-800℃. At this temperature, the carbon source gas is slowly cracked and selectively deposited at the pore, and no deposition occurs outside the pore. The pore size is further refined to be less than 0.33nm. If the temperature is higher than 800℃, the purpose of refinement cannot be achieved, and excessive deposited carbon is generated outside the pore. If the temperature is lower than 600℃, the carbon source gas cannot be cracked and deposited.
[0018] In the above technical scheme, the porous carbon in step 1 is walnut shell-based porous carbon, bamboo-based activated carbon, coconut shell-based porous carbon, peanut shell-based porous carbon, petroleum coke-based porous carbon, needle coke-based porous carbon or activated carbon fiber.
[0019] In the above technical solution, the first carbon source gas in step 1 is methane, benzene vapor, toluene vapor, xylene vapor, ethane, propane or acetylene;
[0020] The second carbon source gas in step 2 is methane, benzene vapor, toluene vapor, xylene vapor, ethane, propane or acetylene;
[0021] Preferably, the first carbon source gas is the same as the second carbon source gas.
[0022] In the above technical scheme, the flow rate of the first carbon source gas in step 1 is 10-500ml / min. If the flow rate of the carbon source gas is too small, the orifice size left in the first chemical vapor deposition will be larger, which will cause a large amount of deposited carbon to enter the pore during the second step of fine-tuning the orifice. If the flow rate of the carbon source gas is too large, the pore will be excessively blocked, and a large amount of invalid deposited carbon will be generated at the orifice, resulting in too low a first coulombic efficiency during sodium storage.
[0023] In the above technical solution, the first insulation time in step 1 is 0-30 minutes and is not 0; the purpose of the first chemical vapor deposition is to quickly reduce the pore opening to prevent the deposited carbon from entering the pore. If the insulation time is too long, it will cause excessive deposition and affect the first coulomb efficiency of sodium storage.
[0024] In the above technical solution, after completing step 1, the size of the orifice can be adjusted to a point where N2 cannot enter most of the orifices but CO2 can enter, that is, the specific surface area of the N2 adsorption and desorption test is 0-100m 2 / g, the specific surface area of CO2 adsorption and desorption test is 100-2000m 2 / g, and the diameter of most pore openings is 0.33-0.364nm.
[0025] In the above technical solution, the flow rate of the second carbon source gas in step 2 is ≥10 ml / min. If the flow rate of the carbon source gas is too small, it will take a long time to fine-tune the orifice.
[0026] In the above technical solution, the duration of the second insulation in step 2 is ≥3h. Since the deposition temperature of the second stage is controlled within a relatively low range, the deposition at this time only selectively occurs at the pore mouth. After the pore mouth is refined, the deposition will not occur. If the deposition time is <3h, the pore mouth cannot be refined, resulting in a lower first coulomb efficiency and a lower sodium storage capacity. Step 2 is controlled at a relatively low reaction temperature. The carbon source gas cracking deposition must occur at a position with a low energy barrier. For porous carbon, the site with a low energy barrier is the pore mouth rich in defects. When the pore mouth position is occupied by deposited carbon, there is no site for carbon source gas cracking deposition, so no deposition will occur even if the time is extended.
[0027] In the above technical solution, after the orifice is refined in step 2, the orifice size of all the holes is closed to the point where CO2 cannot enter, that is, the specific surface area of the CO2 adsorption and desorption test is 0-10m 2 / g, at this time the pore diameters of all pores are less than 0.33nm.
[0028] In the above technical solution, the pore size of the sieved carbon obtained in step 3 is consistent with the pore size of the porous carbon in step 1.
[0029] In the above technical solution, the cooling rate in step 3 is 5-20°C / min.
[0030] Another aspect of the present invention also includes the use of the sieve-type carbon in a negative electrode of a battery.
[0031] In the above technical solution, the sodium storage capacity of the negative electrode of the battery is 350-600 mAh / g, and the first coulomb efficiency is 91-95%.
[0032] Another aspect of the present invention also includes a negative electrode based on sieved carbon, which includes a negative electrode active material, a conductive agent and a binder, wherein the negative electrode active material is the sieved carbon; the conductive agent is SUPER-P, KS-6, conductive graphite, carbon nanotubes, graphene, carbon fiber VGCF, acetylene black or Ketjen black; the binder is PVDF, CMC, SBR, PTFE, SA, PAA or PAN.
[0033] Another aspect of the present invention also includes a battery, including a positive electrode, the negative electrode based on sieve-type carbon, and an electrolyte;
[0034] The active material of the positive electrode is transition metal layered oxide, sodium polyanion compound, Prussian blue or Prussian white.
[0035] The electrolyte includes an organic solvent and a sodium salt, wherein the organic solvent includes EC, PC, DMC, DEC, EMC, EA, FEC or VC; and the sodium salt includes NaClO4, NaPF6, NaBF4, NaFSI or NaTFSI.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention utilizes two step-temperature chemical vapor depositions to prepare screening carbon. In step 1, the first chemical vapor deposition quickly blocks the pores under high temperature conditions (1100-1300°C) to prevent deposited carbon from entering the pore belly, and quickly shrinks the pore mouth to a smaller size at a faster speed. The rapid reduction of the pore mouth actually sacrifices the selectivity of the deposition reaction at the pore mouth and enhances the efficiency of blocking the pore. At this time, deposited carbon will appear around the pore mouth. In step 2, the second chemical vapor deposition is performed under low temperature conditions (600-800°C) to refine the pore mouth to a diameter less than 0.33nm. Since the pore mouth has reached a smaller range after completing step 1, the second chemical vapor deposition carbon can be inhibited from entering the pore, and the deposition at low temperature in step 2 is a selective deposition that only occurs at the pore mouth, and no further deposited carbon will be generated outside the pore.
[0038] 2. The present invention uses two chemical vapor depositions to adjust the pore diameter to less than 0.33 nm while maintaining the original pore size (during the two-step deposition process, the deposited carbon will not enter the pores), thereby effectively improving the first coulombic efficiency of the carbon material and facilitating the commercial application of screening carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The small angle X-ray scattering diagram of Example 1 is shown.
[0040] Figure 2 Shown is the nitrogen adsorption-desorption test diagram of Example 1.
[0041] Figure 3 Shown is the carbon dioxide adsorption and desorption test diagram of Example 1.
[0042] Figure 4 Shown are TEM images of Example 1 before and after the first chemical vapor deposition.
[0043] Figure 5 The figure shows the correlation curve between reaction time and weight gain during the second chemical vapor deposition process of Example 1.
[0044] Figure 6 Shown are TEM images of the porous carbon of Example 1 and the screening-type carbon obtained in Example 1.
[0045] Figure 7 Shown is the first cycle charge and discharge curve of the sodium ion battery negative electrode of Example 1.
[0046] Figure 8 Shown is a small-angle X-ray scattering diagram of Comparative Example 1.
[0047] Fig. 9 Shown is the nitrogen adsorption-desorption test diagram of Comparative Example 1.
[0048] Fig.10Shown is the carbon dioxide adsorption and desorption test diagram of Comparative Example 1.
[0049] Fig.11 Shown is a TEM image of the carbon material of Comparative Example 1.
[0050] Fig.12 Shown is the first cycle charge and discharge curve of the sodium ion battery negative electrode of Comparative Example 1.
[0051] Fig.13 The small angle X-ray scattering diagram of Comparative Example 2 is shown.
[0052] Fig.14 Shown is the carbon dioxide adsorption and desorption test diagram of Comparative Example 2.
[0053] Fig.15 Shown is the TEM image of the carbon material of Comparative Example 2.
[0054] Fig.16 Shown is the first cycle charge and discharge curve of the sodium ion battery negative electrode of Comparative Example 2.
[0055] Fig.17 Schematic diagram of the two-step chemical vapor deposition process of the present invention. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0057] Example 1
[0058] A method for preparing screening carbon comprises the following steps:
[0059] Step 1: First chemical vapor deposition to quickly reduce the pore size: Place porous carbon with rich pore structure into a tube furnace. The porous carbon is activated carbon fiber, and the specific surface area of the small angle scattering test is 1420m 2 / g, nitrogen adsorption and desorption test specific surface area is 1380m 2 / g, the porous carbon has a large specific surface area, indicating that it has abundant pores and more internal space, so it is a large pore belly raw material, and then a protective gas argon gas with a flow rate of 90ml / min is introduced, and the temperature is increased to a final temperature of 1200°C at a heating rate of 10°C / min. Under the final temperature condition of 1200°C, methane gas with a flow rate of 30ml / min is introduced, and the reaction is continued for 25min to quickly reduce the pore size;
[0060] Step 2, the second chemical vapor deposition refines the orifice to a diameter less than 0.33 nm: cut off the methane gas, cool to 700 ° C, introduce methane gas at a flow rate of 10 ml / min, and continue the reaction for 300 min, further refine the orifice to make the orifice diameter less than 0.33 nm;
[0061] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0062] like Figure 1 As shown, the specific surface area of the porous carbon measured by small angle X-ray scattering in step 1 is 1420m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 1415m 2 / g, indicating that the deposited carbon in the two chemical vapor deposition processes did not enter the pore belly, achieving the effect of selectively adjusting the pore opening.
[0063] like Figure 2 As shown in Figure 1, the specific surface area of porous carbon measured by nitrogen adsorption and desorption in step 1 is 1380 m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area is reduced to 30m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area is reduced to 5m 2 / g, indicating that after the first chemical vapor deposition, most of the pore diameters are smaller than 0.364nm (the molecular dynamics diameter of N2), and after the second chemical vapor deposition, the pore diameters of all pores are smaller than 0.364nm.
[0064] like Figure 3 As shown in Figure 1, the specific surface area of the porous carbon measured by carbon dioxide adsorption and desorption in step 1 is 1358 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 600m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 6m 2 / g, indicating that after the rapid reduction of the pore size in step 1, most of the pore diameters are still larger than 0.330nm (the molecular dynamics diameter of CO2). After the fine pore size modification in step 2, the pore diameters of all pores are less than 0.330nm.
[0065] During the first chemical vapor deposition, the rapidly cracked carbon source gas is mainly deposited at the pore mouth, with a small amount of deposition outside the pore, such as Figure 4 As shown, the porous carbon surface does not change much before and after the first chemical vapor deposition, indicating that there is not much carbon deposition outside the pores.
[0066] During the second chemical vapor deposition, the carbon source gas decomposes slowly and selectively deposits at the pore mouth, and no deposition occurs outside the pore, such as Figure 5 As shown, when the weight of the deposited carbon in the secondary deposition reaches the point where the pore mouth is blocked to less than 0.33 nm, the weight gain will not increase no matter how long the reaction time is extended, indicating that the deposition reaction can only occur at the pore mouth.
[0067] like Figure 6 As shown, before and after the two chemical vapor depositions, the internal structure of the pores did not change, and the deposited carbon did not enter the pores, which had a selective effect.
[0068] The negative electrode of the battery is prepared by using the screening type, and the preparation method is as follows:
[0069] The sieved carbon was used as the negative electrode active material, and polyvinylidene fluoride (PVDF) was used as a binder. The PVDF and the conductive agent acetylene black were mixed evenly in a mass ratio of 90:5:5 in an NMP (N-methylpyrrolidone) solvent, coated into an electrode film, and dried at 120°C in a vacuum drying oven for 12 hours. The sieved carbon negative electrode sheet was obtained by rolling and punching. A metal sodium sheet was used as a counter electrode, and 1 mol / L NaPF6 (EC:DEC=1:1) was used as an electrolyte. The sieved carbon negative electrode sheets obtained above were assembled into 2032 button batteries in a glove box, and their electrochemical properties were tested.
[0070] like Figure 7 As shown, it can be seen that the sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 93%, a reversible specific capacity of up to 354 mAh / g, and a low potential platform specific capacity of 280 mAh / g.
[0071] Example 2
[0072] A method for preparing screening carbon comprises the following steps:
[0073] Step 1: First chemical vapor deposition to quickly reduce the pore size: porous carbon (walnut shell-based porous carbon, small angle scattering test specific surface area is 802m 2 / g, nitrogen adsorption and desorption test specific surface area is 798m 2 / g, small pore belly raw material) was put into a tubular furnace, and a protective gas argon gas with a flow rate of 90ml / min was introduced, and the temperature was raised to a final temperature of 1200℃ at a heating rate of 10℃ / min. Under the condition of a final temperature of 1200℃, a methane gas with a flow rate of 30ml / min was introduced, and the reaction was continued for 25min to quickly reduce the pore opening;
[0074] Step 2, the second chemical vapor deposition refinement of the hole mouth to a diameter less than 0.33nm: cut off the methane gas, cool to 700 degrees, introduce methane gas with a flow rate of 10ml / min, and continue the reaction for 300min, further refine the hole entrance to make the hole mouth diameter less than 0.33nm;
[0075] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0076] In this embodiment, the specific surface area of the porous carbon used in step 1 is 802 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 800m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0077] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 798 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 15m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 5m 2 / g, indicating that after the first chemical vapor deposition, most of the pore diameters are smaller than 0.364nm (the molecular dynamics diameter of N2), and after the second chemical vapor deposition, i.e., pore refinement, the pore diameters of all pores are smaller than 0.364nm.
[0078] In this embodiment, the specific surface area of the porous carbon used in step 1 measured by carbon dioxide adsorption and desorption is 780 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 310m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 3m 2 / g, indicating that after the pores are rapidly reduced in step 1, the diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the diameters of all pores are smaller than 0.330 nm.
[0079] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0080] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 94%, a reversible specific capacity of up to 278 mAh / g, and a low potential platform specific capacity of 150 mAh / g.
[0081] Example 3
[0082] A method for preparing screening carbon comprises the following steps:
[0083] Step 1: The first chemical vapor deposition method quickly shrinks the pore size: porous carbon (activated carbon fiber with a small angle scattering test specific surface area of 1420 m 2 / g, nitrogen adsorption and desorption test specific surface area is 1380m 2 / g) was placed in a tubular furnace, and a protective gas argon gas with a flow rate of 90 ml / min was introduced, and the temperature was raised to a final temperature of 1300°C at a heating rate of 10°C / min; at the final temperature of 1300°C, a methane gas with a flow rate of 30 ml / min was introduced, and the reaction was continued for 25 minutes to quickly seal the pore entrance on the porous carbon surface;
[0084] Step 2, the second chemical vapor deposition refinement of the hole to a diameter less than 0.33 nm: cut off the methane gas, cool to 700 ° C, introduce methane gas at a flow rate of 10 ml / min, and continue the reaction for 300 min, further refine the hole entrance to make the hole diameter less than 0.33 nm;
[0085] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0086] In this embodiment, the specific surface area of the porous carbon used in step 1 is 1420 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 1408m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0087] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 21m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 5m 2 / g, indicating that after the rapid shrinkage of the pores in step 1, the diameters of most pores are smaller than 0.364 nm (the molecular dynamics diameter of N2), and after the fine pores in step 2, the diameters of all pores are smaller than 0.364 nm.
[0088] In this embodiment, the specific surface area of the porous carbon used in step 1 was 1358 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 520m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 6m 2 / g, indicating that after the pores are rapidly reduced in step 1, the diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the diameters of all pores are smaller than 0.330 nm.
[0089] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0090] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 92.5%, a reversible specific capacity of up to 348 mAh / g, and a low potential platform specific capacity of 272 mAh / g.
[0091] Example 4
[0092] A method for preparing screening carbon comprises the following steps:
[0093] Step 1: First chemical vapor deposition to quickly reduce the pore size: porous carbon with rich pore structure (coconut shell-based activated carbon, small angle scattering test specific surface area is 1800m 2 / g, nitrogen adsorption and desorption test specific surface area is 1802m 2 / g) was placed in a tubular furnace, and a protective gas argon gas with a flow rate of 90 ml / min was introduced, and the temperature was raised to a final temperature of 1200°C at a heating rate of 10°C / min. Under the condition of a final temperature of 1200°C, a methane gas with a flow rate of 30 ml / min was introduced, and the reaction was continued for 25 minutes to quickly seal the pore entrance on the porous carbon surface;
[0094] Step 2, the second chemical vapor deposition refines the hole to a diameter less than 0.33nm: cut off the methane gas, cool to 800 degrees, introduce methane gas at a flow rate of 10ml / min, and continue the reaction for 300min, further refine the hole entrance to make the hole diameter less than 0.33nm;
[0095] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0096] In this embodiment, the specific surface area of the porous carbon used in step 1 is 1800 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 1760m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0097] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 1802 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 45m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 4.8m 2 / g, indicating that after the rapid shrinkage of the pores in step 1, the diameters of most pores are smaller than 0.364 nm (the molecular dynamics diameter of N2), and after the fine pores in step 2, the diameters of all pores are smaller than 0.364 nm.
[0098] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by carbon dioxide adsorption and desorption to be 1770 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 820m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 7m 2 / g, indicating that after the pores are rapidly reduced in step 1, the diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the diameters of all pores are smaller than 0.330 nm.
[0099] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0100] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 94%, a reversible specific capacity of up to 402 mAh / g, and a low potential platform specific capacity of 325 mAh / g.
[0101] Example 5
[0102] A method for preparing screening carbon comprises the following steps:
[0103] Step 1: First chemical vapor deposition to quickly reduce the pore size: porous carbon with rich pore structure (bamboo-based activated carbon, small angle scattering test specific surface area is 1650m 2 / g, the specific surface area of nitrogen adsorption and desorption test is 1632m 2 / g) was placed in a tubular furnace, and a protective gas argon gas with a flow rate of 90 ml / min was introduced, and the temperature was raised to a final temperature of 1200°C at a heating rate of 10°C / min. Under the condition of a final temperature of 1200°C, a methane gas with a flow rate of 30 ml / min was introduced, and the reaction was continued for 15 minutes to quickly seal the pore entrance on the porous carbon surface;
[0104] Step 2, the second chemical vapor deposition refines the orifice to a diameter less than 0.33 nm: cut off the methane gas, cool to 800 ° C, introduce methane gas at a flow rate of 10 ml / min, and continue the reaction for 300 min, further refine the orifice to make the orifice diameter less than 0.33 nm;
[0105] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0106] In this embodiment, the specific surface area of the porous carbon used in step 1 is 1650 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 1642m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0107] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 1632 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 68m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 5m 2 / g, indicating that after the rapid shrinkage of the pores in step 1, the diameters of most pores are smaller than 0.364 nm (the molecular dynamics diameter of N2), and after the fine pores in step 2, the diameters of all pores are smaller than 0.364 nm.
[0108] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by carbon dioxide adsorption and desorption to be 1624 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 614m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 5m 2 / g, indicating that after the pores are rapidly reduced in step 1, the pore diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the pore diameters of all pores are smaller than 0.330 nm.
[0109] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0110] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 93%, a reversible specific capacity of up to 367 mAh / g, and a low potential platform specific capacity of 290 mAh / g.
[0111] Example 6
[0112] A method for preparing screening carbon comprises the following steps:
[0113] Step 1: First chemical vapor deposition to quickly reduce the pore size: porous carbon with rich pore structure (petroleum coke-based activated carbon, small angle scattering test specific surface area is 2140m 2 / g, nitrogen adsorption and desorption test specific surface area is 2125m 2 / g) was placed in a tubular furnace, and a protective gas argon gas with a flow rate of 90 ml / min was introduced, and the temperature was raised to a final temperature of 1200°C at a heating rate of 10°C / min. Under the condition of a final temperature of 1200°C, a methane gas with a flow rate of 30 ml / min was introduced, and the reaction was continued for 25 minutes to quickly seal the pore entrance on the porous carbon surface;
[0114] Step 2, the second chemical vapor deposition refinement of the hole to a diameter less than 0.33 nm: cut off the methane gas, cool to 800 ° C, introduce methane gas at a flow rate of 10 ml / min, and continue the reaction for 240 min, further refine the hole entrance to make the hole diameter less than 0.33 nm;
[0115] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0116] In this embodiment, the specific surface area of the porous carbon used in step 1 is 2140 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 2122m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0117] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 2125 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 75m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 5m 2 / g, indicating that after the rapid shrinkage of the pores in step 1, the diameters of most pores are smaller than 0.364 nm (the molecular dynamics diameter of N2), and after the fine pores in step 2, the pore sizes of all pores are smaller than 0.364 nm.
[0118] In this embodiment, the specific surface area of the porous carbon used in step 1 is 2100 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 821m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 5m 2 / g, indicating that after the pores are rapidly reduced in step 1, the pore diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the pore diameters of all pores are smaller than 0.330 nm.
[0119] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0120] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 94%, a reversible specific capacity of up to 425 mAh / g, and a low potential platform specific capacity of 350 mAh / g.
[0121] Example 7
[0122] A method for preparing screening carbon comprises the following steps:
[0123] Step 1: First chemical vapor deposition to quickly reduce the pore size: porous carbon with rich pore structure (coconut shell-based activated carbon, small angle scattering test specific surface area is 1800m 2 / g, nitrogen adsorption and desorption test specific surface area is 1802m 2 / g) was placed in a tubular furnace, and a protective gas argon gas with a flow rate of 90 ml / min was introduced, and the temperature was raised to a final temperature of 1200°C at a heating rate of 10°C / min; under the final temperature condition of 1200°C, a natural gas with a flow rate of 30 ml / min was introduced, and the reaction was continued for 25 minutes to quickly seal the pore entrance on the porous carbon surface;
[0124] Step 2, the second chemical vapor deposition refinement of the pore to a diameter less than 0.33 nm: cut off the natural gas, cool to 800 ° C, introduce natural gas at a flow rate of 10 ml / min, and continue the reaction for 240 minutes, further refine the pore entrance to make the pore diameter less than 0.33 nm;
[0125] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0126] In this embodiment, the specific surface area of the porous carbon used in step 1 is 1800 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 1795m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0127] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 1802 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 76m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 3.5m 2 / g, indicating that after the rapid shrinkage of the pores in step 1, the diameters of most pores are smaller than 0.364 nm (the molecular dynamics diameter of N2), and after the fine pores in step 2, the diameters of all pores are smaller than 0.364 nm.
[0128] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by carbon dioxide adsorption and desorption to be 1770 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 350m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 3m 2 / g, indicating that after the pores are rapidly reduced in step 1, the pore diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the pore diameters of all pores are smaller than 0.330 nm.
[0129] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0130] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 95%, a reversible specific capacity of up to 410 mAh / g, and a low potential platform specific capacity of 330 mAh / g.
[0131] Example 8
[0132] A method for preparing screening carbon comprises the following steps:
[0133] Step 1: First chemical vapor deposition to quickly reduce the pore size: porous carbon with rich pore structure (coconut shell-based activated carbon, small angle scattering test specific surface area is 1800m 2 / g, nitrogen adsorption and desorption test specific surface area is 1802m 2 / g) was placed in a tubular furnace, and a protective gas argon gas with a flow rate of 90 ml / min was introduced, and the temperature was raised to a final temperature of 1200°C at a heating rate of 10°C / min; under the final temperature condition of 1200°C, ethane with a flow rate of 30 ml / min was introduced, and the reaction was continued for 25 minutes to quickly seal the pore entrance on the porous carbon surface;
[0134] Step 2, the second chemical vapor deposition refinement of the hole to a diameter less than 0.33 nm: cut off the ethane, cool to 800 ° C, introduce ethane gas with a flow rate of 10 ml / min, and continue the reaction for 240 min, and further refine the hole entrance to make the hole diameter less than 0.33 nm;
[0135] Step 3, turning off the carbon source gas and cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain the screening carbon.
[0136] In this embodiment, the specific surface area of the porous carbon used in step 1 is 1800 m 2 / g, the specific surface area of the sieved carbon obtained in step 3 was measured by small angle X-ray scattering to be 1772m 2 / g, indicating that the deposited carbon from the two chemical vapor deposition phases did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0137] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by nitrogen adsorption and desorption to be 1802 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 46m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 3.9m 2 / g, indicating that after the rapid shrinkage of the pores in step 1, the diameters of most pores are smaller than 0.364 nm (the molecular dynamics diameter of N2), and after the fine pores in step 2, the pore sizes of all pores are smaller than 0.364 nm.
[0138] In this embodiment, the specific surface area of the porous carbon used in step 1 was measured by carbon dioxide adsorption and desorption to be 1770 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 632m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 4m 2 / g, indicating that after the pores are rapidly reduced in step 1, the diameters of most pores are still larger than 0.330 nm (the molecular dynamics diameter of CO2). After the pores are refined in step 2, the diameters of all pores are smaller than 0.330 nm.
[0139] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0140] The sodium ion battery negative electrode prepared in this embodiment has a first coulombic efficiency of up to 93.5%, a reversible specific capacity of up to 408 mAh / g, and a low potential platform specific capacity of 312 mAh / g.
[0141] Comparative Example 1
[0142] This comparative example is compared with Example 1, except that step 2 is not performed in Comparative Example 1.
[0143] The small angle X-ray scattering diagram of the carbon material obtained in Comparative Example 1 is as follows Figure 8 As shown in the figure, it can be seen that the specific surface area of porous carbon measured by small-angle X-ray scattering is 1420m 2 / g, the specific surface area of the carbon material after the pore size is reduced by the above steps is measured by small angle X-ray scattering to be 1418m 2 / g, indicating that after high-temperature rapid deposition, the pore structure of the material has not changed, and the deposited carbon at the entrance of the shrinkage pore has not entered the pore belly.
[0144] The nitrogen adsorption and desorption test diagram of the carbon material provided in Comparative Example 1 is as follows Fig. 9As shown in the figure, it can be seen that the specific surface area of porous carbon measured by nitrogen adsorption and desorption is 1380m 2 / g, the specific surface area of the carbon material after the pore size is reduced by the above steps is reduced to 30m 2 / g, most of the pore diameters are already smaller than 0.364nm (the molecular dynamics diameter of N2).
[0145] The carbon dioxide adsorption and desorption test diagram of the carbon material provided in Comparative Example 1 is as follows Fig.10 As shown in the figure, it can be seen that the specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, the specific surface area of the carbon material after the pore size is reduced by the above steps is reduced to 600m 2 / g, indicating that after the pore size is rapidly reduced in step 1, most of the pore diameters are still larger than 0.330nm (the molecular dynamics diameter of CO2).
[0146] The TEM image of the carbon material provided in Comparative Example 1 is as follows Fig.11 As shown, it can be seen that before and after the pore size is reduced, the internal structure of the pore does not change, and the deposited carbon does not enter the pore belly, achieving a selectivity effect.
[0147] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0148] The first cycle charge and discharge curve of the sodium ion battery negative electrode prepared in this comparative example is as follows Fig.12 As shown, it can be seen that the prepared sodium ion battery split carbon negative electrode material has an initial coulombic efficiency of only 78%, a reversible specific capacity of 258 mAh / g, and a low potential platform specific capacity of 101 mAh / g.
[0149] Comparative Example 2
[0150] This comparative example is compared with Example 1, except that, in the comparative example 2, the reaction time during step 1 is 1 h, and step 2 is not performed.
[0151] like Fig.13 As shown, the specific surface area of porous carbon measured by small angle X-ray scattering is 1420m 2 / g, the specific surface area of the carbon material treated by the steps of Comparative Example 2 was measured by small angle X-ray scattering to be 689m 2 / g, indicating that after high-temperature rapid deposition, the pore structure of the material changes, and the deposited carbon used to shrink the pore mouth partially enters the pores, filling the pores and reducing the pore volume.
[0152] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, the specific surface area of the carbon material after the pore size is partially shrunk in the above steps is reduced to 18m2 / g, indicating that most of the pore diameters are smaller than 0.364nm (the molecular dynamics diameter of N2).
[0153] like Fig.14 As shown in Figure 2, the specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358 m 2 / g, the specific surface area of the carbon material after the pore size is partially shrunk in the above steps is reduced to 500m 2 / g, indicating that some pore sizes are still larger than 0.330nm (molecular dynamics diameter of CO2). At the same time, due to the filling of deposited carbon inside the pore structure, the pore volume decreases and the internal specific surface area decreases significantly.
[0154] TEM images of porous carbon before and after preparation Fig.15 As shown, it can be seen that: before and after the shrinkage of the pore mouth, the internal structure of the pore changes significantly, the deposited carbon partially enters the pore belly, and the deposition selectivity is poor.
[0155] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0156] The first cycle charge and discharge curve of the sodium ion battery negative electrode prepared in this comparative example is as follows Fig.16 As shown, it can be seen that the carbon material obtained in this comparative example has an initial coulombic efficiency of only 45%, a reversible specific capacity of 210 mAh / g, and a low potential platform specific capacity of 54 mAh / g.
[0157] Comparative Example 3
[0158] This comparative example is compared with Example 1, except that, in comparative example 3, the reaction time during step 1 is 2 hours, and step 2 is not performed.
[0159] The specific surface area of porous carbon measured by small angle X-ray scattering is 1420 m 2 / g, the specific surface area of the carbon material after the pore size was partially shrunk by the above steps was measured by small angle X-ray scattering to be 294m 2 / g, indicating that after high-temperature rapid deposition, the pore structure of the material changes, and the deposited carbon used to shrink the pore mouth partially enters the pores, filling the pores and reducing the pore volume.
[0160] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, the specific surface area of the carbon material after the pore size is partially shrunk in the above steps is reduced to 7m 2 / g, indicating that most of the pore diameters are smaller than 0.364nm (the molecular dynamics diameter of N2).
[0161] The specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, the specific surface area of the carbon material after the pore size is partially shrunk in the above steps is reduced to 16m 2 / g, indicating that only a few pore sizes are larger than 0.330nm (the molecular dynamics diameter of CO2).
[0162] Similar to Comparative Example 2, the internal structure changes significantly before and after the pore mouth shrinks, and a large amount of deposited carbon enters the pore belly, causing a large amount of pore structure to disappear.
[0163] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0164] The sodium ion battery negative electrode prepared in this comparative example has an initial coulombic efficiency of only 45%, a reversible specific capacity of 170 mAh / g, and a low potential platform specific capacity of 34 mAh / g.
[0165] Comparative Example 4
[0166] This comparative example is compared with Example 1, except that in Example 4, the temperature of the first chemical vapor deposition in step 1 is 900°C, and the reaction is continued for 25 minutes. Step 2 is the same as Example 1, and the temperature of the second chemical vapor deposition is 700°C, and the reaction is continued for 300 minutes.
[0167] The specific surface area of porous carbon measured by small angle X-ray scattering is 1420 m 2 / g, the specific surface area of the carbon material after the pore size was partially shrunk by the above steps was measured by small angle X-ray scattering to be 1410m 2 / g, indicating that the deposited carbon used to shrink the pore mouth did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0168] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area of the carbon material is reduced to 500m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area is reduced to 21m 2 / g, indicating that after the treatment in step 1, most of the pore diameters are still larger than 0.364nm (the molecular dynamics diameter of N2), and after the treatment in step 2, some pores still have pore diameters larger than 0.364nm.
[0169] The specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area of the carbon material is reduced to 900m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area is reduced to 40m 2 / g, indicating that after the treatment in step 1, most of the pore diameters are still larger than 0.330nm (the molecular dynamics diameter of CO2), and after the treatment in step 2, some pores still have pore sizes larger than 0.330nm.
[0170] Similar to comparative example 1, the internal structure did not change before and after the pore mouth was shrunk, and the deposited carbon did not enter the pore belly, thus achieving a selective effect.
[0171] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0172] The sodium ion battery negative electrode prepared in this comparative example has an initial coulombic efficiency of only 82% and a reversible specific capacity of 304 mAh / g, wherein the low potential platform specific capacity is 230 mAh / g.
[0173] Comparative Example 5
[0174] This comparative example is compared with Example 1, except that, in the comparative example 5, the temperature of the first chemical vapor deposition in step 1 is 1000°C, and the reaction is continued for 25 minutes, and step 2 is the same as Example 1, the temperature of the second chemical vapor deposition is 700°C, and the reaction is continued for 300 minutes.
[0175] The specific surface area of porous carbon measured by small angle X-ray scattering is 1420 m 2 / g, the small angle X-ray scattering of the carbon material obtained after the above steps measured the specific surface area of 1412m 2 / g, indicating that the deposited carbon by two-step chemical vapor deposition did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0176] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 395m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 16m 2 / g, after the first chemical vapor deposition, the pore size of some pores is still larger than 0.364nm (molecular dynamics diameter of N2), and after the second chemical vapor deposition, the pore size of a small number of pores is still larger than 0.364nm.
[0177] The specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 647m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 29m 2 / g, indicating that after the treatment in step 1, most of the pore diameters in the obtained carbon material are still larger than 0.330nm (the molecular dynamics diameter of CO2). After the treatment in step 2, there are still a few pores with pore sizes larger than 0.330nm.
[0178] After two chemical vapor depositions, similar to comparative example 1, the internal structure did not change, and the deposited carbon did not enter the pores, thus achieving a selective effect.
[0179] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0180] The sodium ion battery negative electrode prepared in this comparative example has a first coulombic efficiency of 87%, a reversible specific capacity of 332 mAh / g, and a low potential platform specific capacity of 253 mAh / g.
[0181] Comparative Example 6
[0182] This comparative example is compared with Example 1. Step 1 is the same as Example 1, except that the temperature of the second chemical vapor deposition in Step 2 is 700° C., and the reaction is continued for 2 hours.
[0183] The specific surface area of porous carbon measured by small angle X-ray scattering is 1420 m 2 / g, the specific surface area of the carbon material treated by the steps of Comparative Example 6 was measured by small angle X-ray scattering to be 1420m 2 / g, indicating that the deposited carbon used to shrink the pore mouth did not enter the pore belly, achieving the effect of selectively adjusting the pore mouth.
[0184] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 35m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 16m 2 / g, indicating that after the treatment in step 1, most of the pore sizes are smaller than 0.364nm (the molecular dynamics diameter of N2), and after the treatment in step 2, there are still a few pores with pore sizes larger than 0.364nm.
[0185] The specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, after the first chemical vapor deposition, the specific surface area dropped to 632m 2 / g, after the second chemical vapor deposition, the specific surface area dropped to 241m 2 / g, indicating that after the treatment in step 1, most of the pore diameters are still larger than 0.330nm (the molecular dynamics diameter of CO2), and after the treatment in step 2, there are still a considerable number of pores with pore sizes larger than 0.330nm.
[0186] Before and after the two chemical vapor depositions, similar to Comparative Example 1, the internal structure did not change, and the deposited carbon did not enter the pores, achieving a selective effect.
[0187] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0188] The sodium ion battery negative electrode prepared in this comparative example has a first coulombic efficiency of 79%, a reversible specific capacity of 301 mAh / g, and a low potential platform specific capacity of 212 mAh / g.
[0189] Comparative Example 7
[0190] This comparative example is compared with Example 1. Step 1 is the same as Example 1, except that the temperature of the second chemical vapor deposition in Step 2 is 900° C., and the reaction is continued for 5 hours.
[0191] The specific surface area of porous carbon measured by small angle X-ray scattering is 1420 m 2 / g, the specific surface area of the carbon material after the pore size was partially shrunk by the above steps was measured by small angle X-ray scattering to be 1023m 2 / g, indicating that part of the deposited carbon used to shrink the pore size entered the pore and failed to achieve the effect of selectively adjusting the pore size.
[0192] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area is reduced to 37m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area is reduced to 3m 2 / g, after the treatment in step 1, the pore sizes of most pores are smaller than 0.364nm (molecular dynamics diameter of N2), and after the treatment in step 2, the pore sizes of all pores are smaller than 0.364nm.
[0193] The specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area is reduced to 612m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area is reduced to 4m 2 / g, after the treatment in step 1, most of the pore diameters are still larger than 0.330nm (the molecular dynamics diameter of CO2), and after the treatment in step 2, the pore diameters of all the pores are smaller than 0.330nm.
[0194] Similar to Comparative Example 2, the internal structure changes before and after the pore mouth is shrunk, and the deposited carbon enters the pore belly, failing to achieve a selectivity effect.
[0195] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0196] The sodium ion battery negative electrode prepared in this comparative example has a first coulombic efficiency of 73%. Although the pore diameters are all less than 0.330 nm, the first coulombic efficiency will also be reduced due to excessive carbon deposition. The reversible specific capacity is 278 mAh / g, of which the low potential platform specific capacity is 139 mAh / g.
[0197] Comparative Example 8
[0198] This comparative example is compared with Example 1. Step 1 is the same as Example 1, except that the temperature of the second chemical vapor deposition in Step 2 is 500° C., and the reaction is continued for 5 hours.
[0199] The specific surface area of porous carbon measured by small angle X-ray scattering is 1420 m 2 / g, the specific surface area of the carbon material after the pore size was partially shrunk by the above steps was measured by small angle X-ray scattering to be 1407m 2 / g, indicating that the deposited carbon used to shrink the pore mouth did not enter the pore belly.
[0200] The specific surface area of porous carbon was measured by nitrogen adsorption and desorption to be 1380 m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area is reduced to 37m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area is reduced to 29m 2 / g, indicating that after the treatment in step 1, most of the pore sizes are smaller than 0.364nm (the molecular dynamics diameter of N2).
[0201] The specific surface area of porous carbon measured by carbon dioxide adsorption and desorption is 1358m 2 / g, after the first chemical vapor deposition in step 1, the specific surface area dropped to 596m 2 / g, after the second chemical vapor deposition in step 2, the specific surface area dropped to 274m 2 / g, indicating that after the treatment in step 1, most of the pore diameters are still larger than 0.330nm (the molecular dynamics diameter of CO2). After the treatment in step 2, some pores still have pore sizes larger than 0.330nm. The pore plugging effect of the low-temperature deposition process is poor and the pore size cannot be effectively reduced.
[0202] The 2032 button-type battery was assembled using the same method as in Example 1, and its electrochemical performance was tested.
[0203] The sodium ion battery negative electrode prepared in this comparative example has a first coulombic efficiency of 82%, a reversible specific capacity of 285 mAh / g, and a low potential platform specific capacity of 124 mAh / g.
[0204] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode based on sieve-type carbon, the negative electrode comprising a negative electrode active material, a conductive agent and a binder, wherein: The negative electrode active material is sieve-type carbon; The preparation method of screening type carbon comprises the following steps: Step 1, the first chemical vapor deposition is performed to quickly reduce the pore size: the porous carbon is placed in a chemical vapor deposition device, a predetermined flow rate of protective gas is introduced, the temperature is raised to 1100-1300° C., and then a predetermined flow rate of the first carbon source gas is introduced, the flow rate of the first carbon source gas is 10-500 ml / min, and the first heat preservation is performed, and the duration of the first heat preservation is 0-30 min and is not 0; Step 2, the second chemical vapor deposition is used to refine the orifice to a diameter less than 0.33 nm: after the first heat preservation is completed, the first carbon source gas is cut off, the temperature is lowered to 600-800°C, and a second carbon source gas with a predetermined flow rate is introduced, the flow rate of the second carbon source gas is ≥10 ml / min, and the second heat preservation is performed, and the duration of the second heat preservation is ≥3 hours; Step 3, closing the second carbon source gas and cooling the temperature to room temperature at a predetermined cooling rate to obtain the screening carbon; The pore opening and the periphery of the pore opening of the screening carbon are deposited with primary deposited carbon, and the surface of the primary deposited carbon is deposited with secondary deposited carbon at the position of the pore opening. Both deposited carbons do not enter the pore belly. After the two depositions, the pore opening diameter is less than 0.33nm. The specific surface area of the screening carbon after CO2 adsorption and desorption test is 0-10m 2 / g; The pore diameter of the screening carbon is 0.5-10nm.
2. The negative electrode according to claim 1, characterized in that The porous carbon in step 1 is walnut shell-based porous carbon, bamboo-based activated carbon, coconut shell-based porous carbon, peanut shell-based porous carbon, petroleum coke-based porous carbon, needle coke-based porous carbon or activated carbon fiber.
3. The negative electrode according to claim 1, characterized in that In step 1, the first carbon source gas is methane, benzene vapor, toluene vapor, xylene vapor, ethane, propane or acetylene; The second carbon source gas in step 2 is methane, benzene vapor, toluene vapor, xylene vapor, ethane, propane or acetylene.
4. The negative electrode according to claim 1, characterized in that After completing step 1, the specific surface area of the N2 adsorption and desorption test is 0-100m 2 / g, the specific surface area of CO2 adsorption and desorption test is 100-2000m 2 / g, and the pore diameter is 0.33-0.364nm.
5. The negative electrode according to claim 1, characterized in that After the orifice is refined in step 2, the orifice size of all holes is closed to the point where CO2 cannot enter. The specific surface area of the CO2 adsorption and desorption test is 0-10m 2 / g, and the pore diameters are all less than 0.33nm.
6. The negative electrode according to claim 1, characterized in that The pore size of the sieve-type carbon obtained in step 3 is consistent with the pore size of the porous carbon in step 1.
7. The negative electrode according to claim 1, characterized in that The conductive agent is SUPER-P, KS-6, conductive graphite, carbon nanotubes, graphene, carbon fiber VGCF, acetylene black or Ketjen black, and the adhesive is PVDF, CMC, SBR, PTFE, SA, PAA or PAN.
8. A battery, characterized in that: It comprises a positive electrode, the negative electrode as claimed in claim 1 and an electrolyte.
9. The battery according to claim 8, characterized in that The active material of the positive electrode is a transition metal layered oxide, a sodium polyanion compound, Prussian blue or Prussian white; The electrolyte includes an organic solvent and a sodium salt, wherein the organic solvent includes EC, PC, DMC, DEC, EMC, EA, FEC or VC; and the sodium salt includes NaClO4, NaPF6, NaBF4, NaFSI or NaTFSI.
